Die Linguistic Landscape einer Universität als Ort der Begegnung mit sprachlicher Diversität. Zur visuellen Mehrsprachigkeit an der Universität Oppeln/Opole - Daniela Pelka (Beiträge zur Allgemeinen und Vergleichenden Sprachwissenschaft)
The design of the texts that characterise the linguistic landscape of a university is essentially determined by the needs and expectations of the communication participants using the academic space, who today are often characterised by a relatively high degree of linguistic and cultural diversity. It is not unusual to find Polish-language texts in the linguistic landscape of a university in Poland – such as the University of Opole, which is the focus of this study – where the majority of students and employees have a Polish linguistic and cultural background. However, since the UO is located in a region with a diverse linguistic and cultural tradition and is also claimed by people of different languages and cultures as its direct users, it is also nothing unusual that this landscape also includes texts that are realised in languages other than Polish. This raises the question of what forms these texts take and what functions can be ascribed to them and – following on from this – whether a certain connection can be established between the respective languages and the discourse functions of the signs appearing in them. The answers obtained in turn form the basis for considerations on the extent to which the individual languages correlate with the history and present of the university and its current actors.